2002
DOI: 10.1038/ncb860
|View full text |Cite|
|
Sign up to set email alerts
|

Site of the previous meiotic division defines cleavage orientation in the mouse embryo

Abstract: The conservation of early cleavage patterns in organisms as diverse as echinoderms and mammals suggests that even in highly regulative embryos such as the mouse, division patterns might be important for development. Indeed, the first cleavage divides the fertilized mouse egg into two cells: one cell that contributes predominantly to the embryonic part of the blastocyst, and one that contributes to the abembryonic part. Here we show, by removing, transplanting or duplicating the animal or vegetal poles of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 19 publications
1
45
2
Order By: Relevance
“…Several studies have suggested that differential orientation of early cleavage divisions brings about differential cellular partitioning that influences the distribution of cells at the blastocyst stage (Gardner 1997(Gardner , 2001(Gardner , 2002(Gardner , 2007Piotrowska and Zernicka-Goetz 2001;Bischoff et al 2008). Thus, in the majority of embryos, the first cleavage division is along the AV axis and so distributes both A and V material to both daughter blastomeres (Gulyas 1975;Gardner 1997;Plusa et al 2002Plusa et al , 2005bGray et al 2004). Because of controversy in the early mouse embryo field, it is important to stress that such assessment can be accurate only when the marker of this axis (the second polar body) remains attached to the embryo and before any flow of membrane markers in cytokinesis (Plusa et al 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that differential orientation of early cleavage divisions brings about differential cellular partitioning that influences the distribution of cells at the blastocyst stage (Gardner 1997(Gardner , 2001(Gardner , 2002(Gardner , 2007Piotrowska and Zernicka-Goetz 2001;Bischoff et al 2008). Thus, in the majority of embryos, the first cleavage division is along the AV axis and so distributes both A and V material to both daughter blastomeres (Gulyas 1975;Gardner 1997;Plusa et al 2002Plusa et al , 2005bGray et al 2004). Because of controversy in the early mouse embryo field, it is important to stress that such assessment can be accurate only when the marker of this axis (the second polar body) remains attached to the embryo and before any flow of membrane markers in cytokinesis (Plusa et al 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…Because the plane of the first cleavage division correlates with both the position of the previous meiotic division -the animal pole (Plusa et al, 2002a) and the position of the fertilisation cone that marks the sperm entry Plusa et al, 2002b), the question arises of the extent of the role of the oocyte, and that of the sperm in setting up early embryo patterning. It could be argued that allocation of the progeny of 2-cell blastomeres in diploid parthenogenetic blastocysts differs from that in normal embryos because their animal pole has been perturbed by either cytochalasin treatment or electrofusion.…”
Section: Discussionmentioning
confidence: 99%
“…Fixation by either method was followed by three washes in PBS and 20 minutes of permeabilization with 0.25% Triton X-100 in PBS. Immunostaining was as described previously (Plusa et al, 2002). For detection of Par3, rabbit-anti-Par3 antibody (Lin et al, 2000) was used at a dilution of 1:200 and rhodamine-conjugated secondary anti-rabbit antibody (Jackson ImmunoResearch Laboratories) at a dilution of 1:300.…”
Section: Immunolocalization Of Par3 and Apkc In Preimplantation Embryosmentioning
confidence: 99%